Mirror neurons in e-learning in high school students (Revista Innova Educación, 2021)
Mirror neurons are recognized for their relationship with empathy and that they contribute to virtual education. The objective of the article was to analyze the influence of mirror neurons on virtual learning in upper elementary students of the educational unit "José María Santana Salazar" of the Manta centon. The methodology used was quantitative-qualitative, descriptive, primary, and secondary sources of information were collected, through the deductive and analytical methods. The survey technique applied to an intentional sample of teachers, a student observation card, was used. An interview was applied with an expert in clinical psychology. The results indicated in 59% that mirror neurons promote learning through imitation and in 34% that it improves social relationships through empathy. It is concluded that teachers cannot take advantage of them because they have limited resources to apply them, making it very difficult to motivate and strengthen students' empathy in the virtual context.
Keywords: learning; virtual education; empathy; strategies; mirror neurons